Expression profile of the CSF3 and LPO genes in milk from buffalo (Bubalus bubalis) with and without mastitis - Silva Stella, Aline Aparecida [UNESP]; Simielli Fonseca, Larissa Fernanda [UNESP]; Jovino Gimenez, Daniele Fernanda [UNESP]; Tanamati, Fernanda [UNESP]; Nascimento, Andre Vieira do [UNESP]; Cardoso, Diercles Francisco [UNESP]; Tonhati, Humberto [UNESP] (Elsevier B.V., 2018)
This study compared the expression profile of the candidate genes, CSF3 and LPO, by investigating the immune response mechanisms involved in the phenotype of resistance and susceptibility to mastitis of healthy and infected buffaloes. The Granulocyte Colony Stimulating Factor 3 (CSF3) and Lactoperoxidase (LPO) genes expression profiles were determined in 24 milk samples from buffaloes with (N = 12) and without (N = 12) mastitis, using the quantitative real-time PCR (qRT-PCR) technique. CSF3 and LPO expressions were 5.14 (P = 0.001) and 2.41 (P = 0.097) times higher in animals with mastitis compared to healthy animals, respectively, evidencing a trend toward different expressions of this gene in the studied groups. Our finding suggests that LPO and CSF3 genes are an important defense mechanism against mastitis in dairy buffaloes, and may be putative genes for selecting healthier animals in buffalo breeding programs.
Keywords: Cytokine; Gene expression; Immunity; Mammary gland; Peroxidase